Tamaddun sebagai Konsep Peradaban Islam - Hamid Fahmy Zarkasyi (Universitas Darussalam Gontor, 2015)
This article aims at promoting an appropriate term to depict the substantial meaning of Islamic civilization. Even though there are various terms in Arabic that refer to the meaning of civilization, such as hadârah, tsaqâfah, ‘umrân, the term that substantially compatible with Islam is tamaddun. From a linguistic perspective the root of tamaddun can be traced back to the word dîn, meaning religion. In this case the relation between civilization in the form of scientific movement and political authority with religion is considerably clearer and even provable with historical facts. From the time of the Prophet Muhammad, Umayyad Caliphate, Abbasid Caliphate, until the Ottoman Caliphate the relationship of religion and civilization was manifested. In Islamic history, when Islam entered to a region, the knowledge there will grow rapidly so as to bring prosperity and welfare. When Islam expanded its territory, it did three important stages: First, the expansion of political power dominated by military forces; second, the spreading of religion to the society such Islamic preaching and scientific activity based on al-Qur’an was dominated. Here, the people tried to integrate the teaching of al-Qur’an with the science that comes from other civilizations, especially Greek, Indian, and Persian; third is the spreading of Arabic language to become the official language of science and communication. These three stages proved that the widespread political power in Islamic history was always based on dîn and the development of science, which in turn, becomes civilization of science as well as religion, which defines tamaddun. Therefore, Islam accepted by any nation either non-Muslim or non-Arab for it departed from rational dîn which develops into tamaddun.